Readers and Society in Nineteenth-Century France - Lyons, M. author. aut Link
XI, 208 p.
Keywords: In the nineteenth century, the reading public expanded to embrace new categories of consumers, especially of cheap fiction. These new lower-class and female readers frightened liberals, Catholics and republicans alike. The study focuses on workers, women and peasants, and the ways in which their reading was constructed as a social and political problem, to analyse the fear of reading in nineteenth century France. The author presents a series of case-studies of actual readers, to examine their choices and their practices, and to evaluate how far they responded to (or subverted) attempts at cultural domination.